Konsep Khalifah dalam Al-Qur’an (Kajian Ayat 30 Surat al-Baqarah dan Ayat 26 Surat Shaad) - Rasyad, Rasyad (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2022)
There are three opinions about the caliph, the first is Adam as., Which is a human symbol who serves as the caliph., Second, the caliph means the next generation or successor generation., Third, the caliph is the head of state or head of government. Adam and David in the Qur'an are called caliphs, the difference is; Adam became the caliph for the whole earth at the beginning of human history by replacing a group of jinn who had done damage and bloodshed. While David was only the caliph in a certain area, and was appointed by God as the successor of the kings, leaders, and prophets of the Children of Israel who had preceded him. Caliphate is a function that human beings carry out based on the mandate they receive from God. The mandate is in essence to manage the earth in the best possible way, to prosper the people of the earth, and to eradicate tyranny.ABSTRAKAda tiga pendapat tentang khalifah, pertama adalah Adam as., yang merupakan simbol manusia yang berfungsi sebagai khalifah., kedua, khalifah berarti generasi penerus atau generasi pengganti., ketiga, khalifah adalah kepala negara atau kepala pemerintahan. Adam dan Daud dalam al-Qur’an disebut khalifah, perbedaannya adalah; Adam menjadi khalifah untuk seluruh bumi pada awal sejarah kemanusiaan dengan menggantikan kelompok jin yang telah melakukan kerusakan dan pertumpahan darah. Sedang Daud hanya menjadi khalifah dalam wilayah tertentu saja, dan ditunjuk oleh Tuhan sebagai pengganti dari raja-raja, pemimpin-pemimpin, dan nabi-nabi Bani Israil yang telah mendahuluinya. Khalifah adalah sebuah fungsi yang diemban manusia berdasarkan amanat yang diterimanya dari Allah. Amanat itu pada intinya adalah mengelola bumi dengan sebaik-baiknya, memakmurkan penduduk bumi, serta memberantas kezaliman.